Penanganan Kerusuhan Suporter Sepakbola yang Tidak Sesuai Dengan Standar Operating Procedure (SOP) - I Made Jaya Wiguna; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Warmadewa Press, 2024)
Football is a sport favoured by the Indonesian people. And though it has not yet achieved anything as high as the world, it has been an entertaining spectacle, with many talents in their youth, a stadium with international standards, to huge fans, Excessive fanaticism supported the club's cause of aggressive behaviour that sparked a riot when the pride team lost. As for the problem formula: 1. How is the law handling football fans' riots? 2. How would a member of the police ban for operating a football riot operating out of the standard operating procedure, resulting in loss of life? It's a normative legal research method. As a result of the debate over the management of the football fans' uncontained head of officer no. 1 in the year 2009, section 19 of the FIFA stadium ordinance section 19 b, sanctions from the police's handling of the pro-porter riot are not consistent with the soup of the poll's taking disciplinary justice, general and ethics code. The writer suggests that the government supplement the stadium to international standards with numbered CCTV and extra seats for the game. In this paper, determined that law enforcers on deescalating chaos regarding the people’s safety, must following the standard that given by the legislators to ensure the objectives of law itself, to protect her people.